2021
DOI: 10.1007/s00500-020-05500-8
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method for biometric authentication-oriented face detection using autoregressive model with Bayes Backpropagation Neural Network

Abstract: This paper proposes a novel method, which is coined as ARBBPNN, for biometric-oriented face detection, based on autoregressive model with Bayes backpropagation neural network (BBPNN). Firstly, the given input colour key face image is modelled to HSV and YCbCr models. A hybrid model, called HS-YCbCr, is formulated based on the HSV and YCbCr models. The submodel, H, is divided into various sliding windows of size, 3 9 3. The model parameters are estimated for the window using the BBPNN. Based on the model coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(54 reference statements)
0
3
0
1
Order By: Relevance
“…The proposed method deploys a multilayer perceptron convolution (mlpconv) layer, which mutually updates each parameter at each iteration. Vasanthi and Seetharaman (2021) have proposed the mlpconv neural network and deployed it for parameter estimate; they have reported that the mlpconv neural network yields good results. Therefore, the proposed method is called AGMRF-BDCNN, which is constructed with the Bayesian conception and the AGMRF model is devised into eight Stages with 13 layers.…”
Section: Algorithmic Formulation Of Agmrf-bdcnn Methodsmentioning
confidence: 99%
“…The proposed method deploys a multilayer perceptron convolution (mlpconv) layer, which mutually updates each parameter at each iteration. Vasanthi and Seetharaman (2021) have proposed the mlpconv neural network and deployed it for parameter estimate; they have reported that the mlpconv neural network yields good results. Therefore, the proposed method is called AGMRF-BDCNN, which is constructed with the Bayesian conception and the AGMRF model is devised into eight Stages with 13 layers.…”
Section: Algorithmic Formulation Of Agmrf-bdcnn Methodsmentioning
confidence: 99%
“…The remaining part is arranged as: several works associated with the proposed methodology is elucidated in section 2; the proposed system is presented in section 3; the performance of the proposed methodologies is delineated in section 4; the paper is wrapped up in section 5. (Vasanthi & Seetharaman, 2021) built a technique for biometric-driven facial image recognition centered on multivariate correlation analysis. The features were engendered as a feature tensor matrix.…”
Section: Problem Statementmentioning
confidence: 99%
“…The statistical features-CoV, Skw, and Kur-are computed using the expressions in Eqs. ( 18), (19), and (20), where xi represents intensity value of ith pixel; x represents mean intensity value; N is the number of pixels in the image; σ denotes standard deviation of the intensity values,…”
Section: Dataset and Feature Extractionmentioning
confidence: 99%
“…The ANN surpasses the conventional Bayesian approach and other iterative techniques in pattern classification and segmentation because of the flexibility and suitability of the ANN technique for nonlinearity and dimensionality reduction [14][15][16][17]. The ANN, either independently or combined with the Bayesian rule, provides better results for image analysis [15][16][17][18][19][20]. Si and He [17] have applied an ANN technique to estimate the parameters of the autoregressive model and have reported that the ANN-based parameter estimate yields better results than the maximum likelihood, Bayes, and iterative methods.…”
Section: Introductionmentioning
confidence: 99%